MORFOFONOLOGI KATA POLIMORFEMIK BERKONSTRUKSI MORFEM DASAR BERAKHIR VOKAL DAN MORFEM TERIKAT {-AN} DALAM BAHASA INDONESIA (THE MORPHOPHONEMIC PROCESS ON POLIMORPHEMIC MORPHEMES OF VOWEL ENDED WORDS AND BOUND MORPHEMES {-AN} IN BAHASA INDONESIA) - Cahyo Yusuf; Rangga Asmara; Yusup Irawan; Widya Ratna Kusumaningrum (Metalingua: Jurnal Penelitian Bahasa, 2021)
The study aimed to investigate: (1) the existence of glottal stop consonants [?], voiced palatal or semivowel consonant [y] and bilabial semivowel consonant [w] in the polymorphemic words with vowel endings of bound morphemes [-an], and (2) the non-existence of glottal stop consonants [?], voiced palatal or semivowel consonant [y] and bilabial semivowel consonant [w] in the polymorphemic words with vowel endings of bound morphemes [-an]. The data were collected from selected participants who represented and met the qualification as native Indonesian speakers. To gather the data, the study used recording and observation techniques which were analyzed speech analyzer Praat by implementing (a) acoustic approach, i.e., analysing the segmentals by using Praat, and (b) inductive method in which it compared the interpretative results of the researchers and the segmental acoustic from Praat. The results showed that (a) the glottal stop consonant [?], voiced palatal or semivowel consonant [y] and bilabial semivowel consonant [w] were identified in the polymorphemic words with vowel endings of bound morphemes [-an] and (b) in the polymorphemic words with vowel endings of bound morphemes [-an] have phoneme-loss of the glottal stop consonant [?], voiced palatal or semivowel consonant [y] and bilabial semivowel consonant [w] in comparison its derivative sounds of the words with any free morphemes and bound morphemes [-an]